Template determines whether chemically identical nanoparticle scaffolds show elastic recovery or plastic failure - Suresh, Karthika; Patil, Shivprasad; Rajamohanan, Pattuparambil Ramanpillai; Kumaraswamy, Guruswamy (Langmuir, 2016)
Subtle variations in the preparation of ice-templated nanoparticle assemblies yield monoliths that are chemically identical but exhibit qualitatively different mechanical behavior. We ice template aqueous dispersions to prepare macroporous monoliths largely comprising silica nanoparticles held together by a crosslinked polymer mesh. When the polymer is crosslinked in the presence of ice crystals, we obtain an elastic sponge that is capable of recovery after imposition of large compressive strains (up to 80%). If, however, the ice is lyophilized before the polymer is crosslinked, we obtain a plastic monolith that fails even for modest strains (less than 10%). The elastic sponge and the plastic monolith are chemically identical; they have the same organic content, the same ratio of polymer to crosslinker, and the same average crosslink density. Atomic force microscopy (AFM) was used to probe the local mechanical properties of the crosslinked polymer mesh. These measurements indicate that plastic monoliths dissipate significantly more energy and have a larger spatial variation in local mechanical response relative to the elastic sponges. We believe that this behavior might correlate with a wider spatial distribution of crosslinks in plastic scaffolds relative to elastic scaffolds.

Three-dimensional printing with waste high-density polyethylene - Gudadhe, Aniket; Bachhar, Nirmalya; Kumar, Anil; Andrade, Prem; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2019)
Fused filament fabrication (FFF) three-dimensional (3D) printing of semicrystalline polymers such as high density polyethylene (HDPE) is challenging because crystallization-induced shrinkage of the filament, as it cools, results in stresses that warp the printed part and debond it from the print substrate. Here, we demonstrate that waste-derived HDPE can be successfully 3D printed by (i) blending with a small fraction (<0.5% by weight) of dimethyl dibenzylidene sorbitol (DMDBS) and (similar to 10%) linear low density polyethylene (LLDPE) and (ii) printing the object with a thin ``brim'' around it that is adhered to the print substrate using common polyvinyl acetate-based glue. We match our experimental results with FEM simulations that provide insight into the origin of the stresses developed during printing. Because HDPE forms a significant fraction of the plastic waste stream, conversion of waste-derived HDPE to 3D printing filament has important technological implications.
Keywords: 3d printing polyethylene printing; polymer blend; Recyclability; warpage

Thermal properties of polyethylene-grafted sheetlike silsesquioxanes - Sharma, Vivek; Paulbudhe, Uday; Gupta, Poonam; Zalte, Akshat Shirish; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2025)
Polyethylene-grafted layered silsesquioxanes, termed polyethylene-clays (PEC), are nanocomposites comprising polyethylene chains tethered to inorganic sheets with a phyllosilicate-like structure. Here, we report that these nanocomposites show two-stage crystallization on cooling, qualitatively different from previous reports on polyethylene nanocomposites. We employ differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) to study the melting and crystallization of PEC. End tethering of the polyethylene chains to a nanosheet strongly influences the manner in which PEC crystallizes from the melt on cooling. PEC exhibits two-step crystallization, characterized by a sharp high-temperature exotherm, followed by a broader exotherm at lower temperatures, in contrast to a single sharp exotherm for neat polyethylene. SAXS indicates that lamellar stacks form at high temperatures and that the low-temperature exotherm corresponds to the formation of additional lamellae and their insertion within these stacks. PEC exhibits lower peak melting temperature, lower crystallinity, and a wider melting range relative to polyethylene. We show that the progress of crystallization of PEC is determined by its ultraslow relaxation dynamics. In contrast, PEC in xylene solution exhibits a significantly shorter relaxation time than the melt PEC. Such systems exhibited a single exotherm on cooling and SAXS structure factor peaks with peak positions in a ratio of 1:2. We hypothesize that the high melt viscosity inhibits the crystallization-induced decrease in the specific volume of PEC, resulting in tensile internal stresses that determine the observed thermal behavior.
Keywords: clay; Crystallization; Nanocomposite; Polyethylene; silsesquioxane